Validation and invalidation of SARS-CoV-2 main protease inhibitors using the Flip-GFP and Protease-Glo luciferase assays - Chunlong Ma; Haozhou Tan; Juliana Choza; Yuyin Wang; Jun Wang (Elsevier, 2022)
SARS-CoV-2 main protease (Mpro) is one of the most extensively exploited drug targets for COVID-19. Structurally disparate compounds have been reported as Mpro inhibitors, raising the question of their target specificity. To elucidate the target specificity and the cellular target engagement of the claimed Mpro inhibitors, we systematically characterize their mechanism of action using the cell-free FRET assay, the thermal shift-binding assay, the cell lysate Protease-Glo luciferase assay, and the cell-based FlipGFP assay. Collectively, our results have shown that majority of the Mpro inhibitors identified from drug repurposing including ebselen, carmofur, disulfiram, and shikonin are promiscuous cysteine inhibitors that are not specific to Mpro, while chloroquine, oxytetracycline, montelukast, candesartan, and dipyridamole do not inhibit Mpro in any of the assays tested. Overall, our study highlights the need of stringent hit validation at the early stage of drug discovery.